Evaluasi Implementasi Sistem Informasi Manajemen Rumah Sakit (SIMRS) Rekam Medis dengan Metode Problem Solving Tools di Rumah Sakit X - Rahmaddian, Tosi; Faaghna, Laiza (Jurnal Kesehatan, 2023)
Hospitals throughout Indonesia have been required to use SIMRS, which is easy to use and able to handle problems that arise in their services. An evaluation of the implementation of the Hospital Management Information System (SIMRS) for medical records was carried out to determine improvement strategies for integrating all services. The aim of this study is to evaluate the implementation of the Hospital Management Information System (SIMRS) Medical Records using the Problem-Solving Tools method at Hospital. This research used a qualitative approach with a descriptive design. Information on this qualitative approach is obtained through problem-solving tools and in-depth interviews. The components studied are problem identification, problem cause analysis, problem-solving alternatives, and problem-solving priorities. During the problem identification, there are some problems found in the doctor's schedule and booking system, there was no user to input drug transactions, electronic prescriptions in pharmacies were not yet integrate, and there were no operational service standards. Based on an analysis of the causes of problems, the causes were found in man, method, money, and materials, which were still problematic. The alternatives of problem solving were carried out based on the existing problem. Then a problem-solving priority is chosen, namely, that hospital management commits to the medical committee regarding the discipline of the specialist doctor's service schedule. So, it is concluded that medical records can be made conventionally (in writing) or electronically at Hospital X. Medical record data is inputed electronically because it is integrated with SIMRS. To overcome the problems that exist in the implementation of SIMRS medical records, hospital management needs to commit to the medical committee regarding the discipline of the doctor's service schedule, determine providers who will use the booking system, and coordinate with the foundation regarding the implementation of SIMRS.